A Strongly Inherited Familial Symphalangism of All the Proximal Interphalangeal Joints. (10th November 2020) - Nightingale, Craig; Kyprianou, Katerina; Syed, Mobin
Symphalangism is a rare congenital condition resulting in ankylosis of the interphalangeal joints to a varying degree. This can lead to significantly reduced function of the hand. The condition is difficult to assess in infants due to lack of radiographical evidence, and as such thorough history and examination is crucial. Treatment options include conservative and surgical management. It is difficult to achieve full range of movement in more advanced cases, but significant improvements have been noted in less severe cases. Best results are seen when patients are treated before the age of 2 years. This is a case of a inherited symphalangism with a strong family history, and their decision to manage this problem conservatively. In these cases, a strong input from physiotherapy and occupational therapy is the mainstay of management.